Sexuality and Intimacy Needs Within a Hospitalized Palliative Care Population: Results From a Qualitative Study. (April 2022) - Kelemen, Anne; Van Gerven, Clara; Mullins, Katherine; Groninger, Hunter
Background: Palliative care (PC) clinicians are well trained to address physical, psychosocial and spiritual needs of patients who have a serious illness. However, one area that is often overlooked is intimacy and sexuality. Objective: To explore patient concerns regarding intimacy as it relates to illness, family reactions, physician conversations, and coping strategies and challenges. Methods: Eligible subjects (at least 18 years old, capacitated, receiving PC consultation at the lead author's institution) participated in semi-structured interviews between November and December 2017. Transcripts were open-coded and analyzed using Dedoose 3.5.35 software. A constant comparative method was used to identify patterns in the data. Results: 21 interviews were analyzed and several themes emerged. Participants described the effect of physical and mental/emotional changes on their relationships. Family relationships, romantic relationships, and sexuality were prominent in patients' experiences of intimacy and how it changed as the illness progressed. Relationships were often noted to strengthen during the course of illness, while sexual activity was frequently reported to be negatively impacted. Patients consistently reported little provider communication on the impact of illness on intimacy beyond instructions about what sexual activities they could or could not engage in. Conclusion: This study underlines the significant impact of serious, progressive illness on relationships, sexuality, and physical and emotional intimacy. It highlights that these topics continue to be priorities for patients with serious illness, and that medical teams frequently fail to address them at all. Future research should further explore these issues across diverse patient populations.